Having an injury complaint during the four weeks before an international athletics (`track and field`) championship more than doubles the risk of sustaining an injury during the respective championship: a cohort study on 1095 athletes during 7 international championships - Edouard, P.; Junge, A.; Alonso, J. M.; Timpka, T.; Branco, P.; Hollander, K. (Journal of Science and Medicine in Sport, 2022)
Objectives: To analyse the association between pre-participation health status and in-championships injuries in a large dataset from seven international athletics championships, and to determine the health status of athletes during the four weeks before the start of international athletics championships. Design: Prospective cohort study. Methods: We used data collected from athletes of national teams with medical staff who participated i) in a pre-participation health survey (retrospective data collection) and ii) in an in-championships injury surveillance (prospective data collection) during seven international athletics championships (2013-2018). We performed a binomial logistic regression with in-championship injury (yes/no) as the dependent variable and sex, age, discipline (explosive/endurance), type of championships (outdoor/indoor) and pre-participation injury complaint (yes/no) and pre-participation illness complaint (yes/no) as independent variables, with odds ratios (OR) and 95% confidence intervals (95% CI). Results: Out of the 1095 athletes included 31.2% reported an injury complaint during the 4 weeks before the championships and 21.6% an illness complaint. The univariate model showed that discipline, type of championships and pre-participation injury complaints (OR=2.57, 95%CI: 1.66 to 3.97) were significantly associated with in-championships injuries, and the multivariable model showed that type of championships and pre-participation injury complaints (OR=2.64, 95%CI: 1.60 to 4.36) remained significantly associated with in-championships injuries. Conclusions: Our present study shows that an injury complaint during the four weeks before an international athletics championship significantly increased risk of sustaining an injury during the following championship, which was reported by about one third of athletes with differences between sex and disciplines.